Optimalisasi Konsentrasi Demulsifier pada Proses Demulsifikasi MInyak Mentah dalam Slop Oil - Resti, Ade; Kusumastuti, Ella; G, Agnesya Putri; Jumaeri, Jumaeri; Wijayati, Nanik (Indonesian Journal of Chemical Science, 2020)
Recovery of the crude oil component in slop oil has the potential to increase the economic value of the slop oil component of the crude oil obtained can be reprocessed, with the demulsification process using two kinds of demulsifiers are Dem-02 and Dem-17. The purpose of this research is to study the variations in demulsifier added to the separated water, and effect of optimum concentration to characterize the crude oil added to viscosity, density, %BS&W, water content, oil content, ash content and metal content (Al, Fe, Ca and Si ) after warming up 24 hours. The results showed the amount of concentration variation of the demulsifier affected the amount of the percentage of water seperation. The more concentrations added the more water water sparation. The optimal demulsifier concentration is at 16.000 ppm. The results of SO-01 and SO-02 slop oil characterization before demulsification each had viscosity of 79.0861 cSt and 408.4904 cSt, density of 0.9842 gr / mL and 0.9806 gr / mL, percentage of BS&W 90% and 80% , ash content 0.9376% and 0.9619%. After demulsification of viscosity 10.2124 cSt and 37.0041, density 0.9052 mg / mL and 0.9119 gr / mL, BS&W percentage 30%, oil content 0.8350% and 1.0505%, water content 19.2% , ash content 1.8869% and 1.8822%. Al, Fe, Ca and Si metal content in slop oil. After demulsification increases with increasing ash content slop from demulsification.